A market failures approach to justice in health. (May 2022) - Horne, L. Chad; Heath, Joseph
It is generally acknowledged that a certain amount of state intervention in health and health care is needed to address the significant market failures in these sectors; however, it is also thought that the primary rationale for state involvement in health must lie elsewhere, for example in an egalitarian commitment to equalizing access to health care for all citizens. This paper argues that a complete theory of justice in health can be derived from a commitment to correcting market failure, or in other words promoting Pareto-efficiency, in the domain of health. This approach can address familiar problems around access to care, as well as problems related to resource allocation and rationing (including resource allocation between generations), the control of health care costs, and the foundations of public health. Egalitarian theories of justice in health cannot make sense of the depth and pervasiveness of state involvement in health and health care; only a theory rooted in the need to correct market failure can.